2003
DOI: 10.1081/ja-120024235
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent's Suicide Attempts: Populations at Risk, Vulnerability, and Substance Use

Abstract: Adolescence corresponds to a transition period that requires adaptation and change capacities and skills. Most young people succeed with this challenge, whereas a minority fail. In order to identify with the teenage culture, become autonomous, and differentiate from their parents, some adolescents choose to use drugs, beginning with the use of cigarettes, alcohol, cannabis, followed by other illicit drugs such as opiates and stimulants. A high proportion of these adolescents attempt suicide, which is the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
2
19
0
2
Order By: Relevance
“…Even low levels of tobacco use have been associated with increased suicidal behaviors (6). Co-morbidity increased the risk for suicidal behaviors, especially substance use disorders with mood disorders (11,13). Wagner et al (17) found that adolescents with depression were at a greater risk for attempted suicide, when they also had a comorbid alcohol use disorder.…”
Section: Adolescent Suicide Alcohol and Substance Abusementioning
confidence: 98%
See 1 more Smart Citation
“…Even low levels of tobacco use have been associated with increased suicidal behaviors (6). Co-morbidity increased the risk for suicidal behaviors, especially substance use disorders with mood disorders (11,13). Wagner et al (17) found that adolescents with depression were at a greater risk for attempted suicide, when they also had a comorbid alcohol use disorder.…”
Section: Adolescent Suicide Alcohol and Substance Abusementioning
confidence: 98%
“…Suicidal behavior results from a convergence of several risk factors and the absence of several protective factors (13). A model of suicidal behavior among individuals with alcoholism has recently been proposed (14).…”
Section: Adolescent Suicide Alcohol and Substance Abusementioning
confidence: 99%
“…Thus, it is important to more fully understand the risk factors in order to develop procedures for early intervention. The present study examines the mediating role of psychological distress (depression and social withdrawal) in the relationship between two primary vulnerability factors, interpersonal dependency and self-criticism in suicidality, including ideation, reported intention, and past attempts as indicators of suicidality (e.g., Ash, 2006;Bolognini, Plancherel, Laget, & Halfon, 2003;Joiner et al, 2005;King et al, 2001;Roberts, Roberts, & Chen, 1998).…”
Section: Suicidality In Adolescencementioning
confidence: 99%
“…Esse é momento propício ao surgimento do consumo de drogas, pois, como o indivíduo ainda não desenvolveu de forma adequada algumas habilidades, pode ser estimulado ao uso de cigarros, álcool, maconha até ao consumo de múltiplas drogas ilícitas (1)(2) .…”
Section: Introductionunclassified